Genetic testing for hereditary hyperparathyroidism and familial hypocalciuric hypercalcaemia in a large UK cohort. (12th June 2020) - Mariathasan, Sashi; Andrews, Katrina A.; Thompson, Edward; Challis, Ben G.; Wilcox, Sarah; Pierce, Heather; Hale, Julia; Spiden, Sarah; Fuller, Gavin; Simpson, Helen L.; Fish, Brian; Jani, Piyush; et al.
Abstract: Background: Primary hyperparathyroidism (PHPTH) is a common endocrine disorder and an estimated 10% of cases are hereditary, related to syndromes including; multiple endocrine neoplasia (MEN) type 1, MEN type 4, MEN2A and hereditary hyperparathyroidism‐jaw tumour syndrome. Establishing the underlying genetic cause for PHPTH allows for personalized and cost‐effective management. Familial hypocalicuric hypercalcaemia (FHH) is a benign disorder of hypercalcaemia associated with an inappropriately low urinary calcium excretion, which is quantified by the calcium creatinine clearance ratio (CCCR). Recent NHS England National Genomic Test Directory testing criteria for familial hyperparathyroidism state testing patients presenting with PHPTH and CCCR > 0.02 presenting (i) <35 years of age, or (ii) <45y with one of (a) multiglandular disease, or (b) hyperplasia on histology, or (c) ossifying fibroma(s) of the maxilla and/ or mandible, or (d) a family history of unexplained PHPTH. The testing criterion for FHH is a CCCR < 0.02. Aims and Methods: A retrospective review of patients referred for genetic testing over a 4 year period for suspected hereditary HPTH was performed. Genetic analysis was performed by next‐generation sequencing of the following genes; MEN1, CDC73, CASR, CDKN1A, CDKN1B, CDKN2B, CDKN2C, RET, GCM2, GNA11, and AP2S1 in NHS‐accredited Regional Genetic laboratories. Aims of this study were to better define testing criteria for suspected hereditary PHPTH in a UK cohort. Results: A total of 121 patients were included in this study (92 female) with a mean age of 41 years (SD 17). A pathogenic germline variant was identified in 16% (n = 19). A pathogenic variant was identified in the PHPTH genes CDC73 in a single patient and MEN1 in six patients (6% of total), in the FHH genes, CASR in 11 patients and AP2S1 in a single paediatric case (10% of total). A variant of uncertain significance (VUS) was identified in eight patients (6%) but over the course of this study familial segregation studies and computational analysis enabled re‐classification of four of the variants, with two VUS's in the CASR gene being upgraded to likely pathogenic variants. Age at diagnosis and multiglandular disease as sole risk factors were not predictive of a pathogenic germline variant in this cohort but a positive family history was strongly predictive ( P  = .0002). A significant difference in the mean calcium creatinine clearance ratio (CCCR) in those patients with an identified CASR pathogenic variant versus those without ( P  = .0001) was demonstrated in this study. Thirty‐three patients were aged over 50 years and the diagnostic rate of a pathogenic variant was 15.1% in those patients >50 years of age compared to 15.9% in those <50 years. Five patients >50 years and with a CCCR of <0.01, were diagnosed with a pathogenic variant in CASR . Conclusion: Family history was the strongest predictor of hereditary PHPTH in this cohort. This study has highlighted the importance of re‐evaluating VUS's in order to inform patient management and enable appropriate genetic counselling. Finally, this study has demonstrated the need to consider genetic testing for PHPTH in patients of any age, particularly those with additional risk factors.